Making Wine like Iberians: a Learning Experience with the International Workcamp at La Ciutadella Ibèrica of Calafell - Manel Gómez Gutiérrez; J. Pou Vallès; O. Saura (EXARC Journal)
The Youth Department of the Autonomous Government of Catalonia organises international summer workcamps in the region. Basically these workcamps consist of different projects where young people participate doing voluntary work as services to the local community, helping people, nature protection or practical work on historical heritage among others. In the framework of the 2014 workcamp, our proposal was to focus work on one of the aspects of the Iberian culture that has been more investigated lately: the production of wine.